The ways to improve the efficiency of the use of integrated marketing communications for the formation of a national brand of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
The concepts of methods of forming and use of the brand communicationtools has importance not only in large companies and organizations,but also in the general structures of country brand. Branding of the country- a strategic decision that requires national zeal and thorough investigation,since the state of the brand depends on the general condition ofthe people, its economy, financial and tourist attraction, the state and thecountry’s competitiveness. Therefore, in this article are provided especiallyfor tools of integrated marketing communications for the formation of thecountry brand of Kazakhstan. The article includes the history and conceptof country brand. Analyzing the importance of building a country brand,suggested building a national brand, which consists of the attributes ofthe Republic of Kazakhstan. There are missions and especially the use ofintegrated marketing communication. And in particular the use listed intergrirovanmarketing communication for the formation of the Country BrandRepublic of Kazakhstan.